Representasi Stereotype Maskulinitas Pria dalam Relasi Antar Kelas di Iklan Total Care - Muhammad Nurcholis Rokan; Aditya Putra Tri Anggara; Fikri Abdul Kholik; Fajar Junaedi (ANALOGI Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to explore the stereotypical representation of male masculinity in interclass relations shown in Total Care advertisements. This topic was chosen because advertisements have a significant impact on people's perceptions of gender and social class. The research method used was to collect data from various Total Care advertisements aired in the mass media and conduct qualitative analysis with a semiotic approach. The research shows that these advertisements tend to portray strong and dominant masculinity, with male characters portrayed as protectors and providers. In addition, there is a difference in representation between upper-class men and lower-class men, where upper-class men are often depicted in the context of power and success, while lower-class men are often depicted in the context of weakness and dependence. The conclusion of this study confirms that Total Care advertisements not only reflect stereotypes of masculinity, but also reinforce power relations between social classes. This research is important to understand how the media contributes to the formation of gender and class identities in society. This research is also expected to be a reference for further research on the influence of media on gender and social class perceptions.